Analisis Pengaruh Fleksibilitas Pengelolaan KeuanganTerhadap Kinerja Keuangan Badan Layanan Umum Sebelum Dan Sesudah Penerapan PPK-BLU (Kasus pada RSUP Dr. Sardjito Yogyakarta) - , Etika Wijayaningrum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Public Service Agencyâs Financial Management (PPK-BLU) provides flexibility in managing its finance for the government agencies which have turned into BLU. PPK-BLU allows the agency to directly spend its revenues for financing its operational activity and also for investing purposes without any obligation to deposit fund to state treasury account, as well as its surplus. Flexibility in managing its finance for BLU is based on economical, productive and good corporate governance principle. PPK- BLU concept is to achieve professionalism, entrepreneurship, transparency and accountability in public services. RSUP Dr. Sardjito Yogyakarta is one of the government hospitals which has declared as fully BLU and implementing general accounting standard for hospital based on the Indonesian Accountant Association and hospital accounting standard which is determined by the Department of Health of The Republic of Indonesia. The purpose of this thesis is to observe the difference in financial performance before and after implementing PPK-BLU which provides flexibility in managing its finance. Valuing the performance in finance before and after implementing PPK-BLU could be done by conducting a financial statement analysis and calculating ratios. Valuing hospitalâs performance in finance of BLU RSUP Dr. Sardjito could be done by observing financial ratios which have close relation to management efficiency level in assets management in order to have a better quality and quantity of public service, solvency ratio which can support long-term obligation, liquidity ratio which can support short-term obligation and profitability ratio, even though RSUP Dr. Sardjito is a public hospital stand as non- profit corporation. Performance in finance of BLU RSUP Dr. Sardjito Yogyakarta after implementing PPK-BLU has been come be better, it can be seen from ratios which have impact on operational management efficiency. It shows that PPK- BLU goal in having more efficient, effective and productive corporation can be well implemented by RSUP Dr Sardjito managers. However, having better performance in finance for BLU RSUP Dr. Sardjito is a result of amount of untight contribution from state budget (APBN) to finance operational expenditures and general administrations.